Konflik Perebutan Lahan Kereta Api: Dilema Penguasaan Aset Negara Pasca Nasionalisasi - Wardojo, Waskito Widi (Perkumpulan Program Studi Sejarah Se-Indonesia, 2024)
This research explains the conflict over railway land and the dilemma of controlling state assets after nationalization. The research results show that there is a gap in understanding between the state and society regarding the history of land ownership. There is a perception that if land has been used for more than a few years, it can be transferred to individual ownership. In several cases, in big cities such as Medan, Bandung, and Jakarta, there is a tendency to involve the business interests of certain individuals or communities with strong capital. This indicates that in the case of the second classification, the state is challenged by capitalist forces with a pure profit orientation, while the public interest and public social services tend to be ignored. The emergence and strengthening of regional institutions as a result of growing autonomy in government also has the potential for conflicts of interest with PT. KAI regarding ownership of its assets. In this case, it is not surprising that a dispute involving the two of them becomes a conflict of interest between the central and regional governments.